Red eyes: COVID-19 or Microbial infection - Hussein Katai Abdul Sada,; Salah Zuhair Abed Al Asadi,; Ahmed Mohammed Alsamak,; Amaleed Abduljaleel Alkadhem, (Journal of the Pakistan Medical Association, 2023)
Objective: To identify the source of eyes infections during coronavirus disease-2019 pandemic. Method: The cross-sectional study was conducted at the Al-Basrah Teaching Hospital, Iraq from March 2 to September 24, 2020, and comprised eye swabs from patients having confirmed diagnosis of coronavirus disease-2019. The swabs were subjected to microbiological and molecular examinations. They were cultivated on blood agar and savoured dextrose agar plates to detect the types of microbes and then confirmed by genetic analysis using polymerase chain reaction. Chi-square was used to identify the differences between samples who had symptoms or those who had no symptoms p Less than or Equal to 0.05 was considered significant. Results: Of the 213 patients quarantined with coronavirus disease-2019, there were 98(46%) males and 115(54%) females. Of them, 22(10.3%) had red eyes; 10(45.45%) males and 12(54.54%) females, with overall age ranging 18-74 years. Streptococcus pneumonia was detected in 8(36.6%) patients, followed by staphylococcus aureus and candida albicans 5(22.7%) each, and haemophilus influenzae 3(13.6%). Conclusion: Red eyes of some patients with coronavirus disease-2019 may have been caused by secondary infection. Keywords: Agar, Staphylococcus aureus, Photophobia, Polymerase chain reaction, Glucose, Pruritus.